Review of experimental investigations of wings in ground effect at low Reynolds numbers - Lee, T.; Lin, G. (Frontiers in Aerospace Engineering, 2022)
The ground effect-induced large lift increase and lift-induced drag reduction have long been recognized and utilized in the design and construction of wing-in-ground effect (WIG) craft. Various wing planforms have been employed in WIG craft. In this study, the experimental investigations of rectangular wings and delta wings of reverse and regular configurations at low Reynolds numbers are reviewed. For rectangular wings, both chord-dominated and span-dominated ground effects on the aerodynamics, tip vortex, and lift-induced drag are reviewed. For reverse delta wings, in addition to the experimental measurements of the aerodynamics and tip vortex flow at different ground distances, passive flow control utilizing Gurney flap, cropping, and anhedral are reviewed. The impact of ground effect on delta wings is also discussed. Suggestions for future investigations applicable to each wing planform in-ground effect are provided.